Seneca Valley Virus 3C Protease Inhibits Stress Granule Formation by Disrupting eIF4GI-G3BP1 Interaction - Wen, Wei; Zhao, Qiongqiong; Yin, Mengge; Qin, Liuxing; Hu, Junjie; Chen, Huanchun; Li, Xiangmin; Qian, Ping (Frontiers in Immunology, 2020)
Stress granules (SGs) are the sites of mRNA storage and related to the regulation of mRNA translation, which are dynamic structures in response to various environmental stresses and viral infections. Seneca Valley virus (SVV), an oncolytic RNA virus belonging to Picornaviridae family, can cause vesicular disease (VD) indistinguished from foot-and-mouth disease (FMD) and other pig VDs. In this study, we found that SVV induced SG formation in the early stage of infection in a PKR-eIF2α dependent manner, as demonstrated by the recruitment of marker proteins of G3BP1 and eIF4GI. Surprisingly, we found that downregulating SG marker proteins TIA1 or G3BP1, or expressing an eIF2α non-phosphorylatable mutant inhibited SG formation, but this inhibition of transient SG formation had no significant effect on SVV propagation. Depletion of G3BP1 significantly attenuated the activation of NF-κB signaling pathway. In addition, we found that SVV inhibited SG formation at the late stage of infection and 3C protease was essential for the inhibition depending on its enzyme activity. Furthermore, we also found that 3C protease blocked the SG formation by disrupting eIF4GI-G3BP1 interaction. Overall, our results demonstrate that SVV induces transient SG formation in an eIF2α phosphorylation and PKR-dependent manner, and that 3C protease inhibits SG formation by interfering eIF4GI-G3BP1 interaction.